Trends in Incidence and Mortality of Waldenström Macroglobulinemia: A Population-Based Study - Yin, Xuejiao; Chen, Lei; Fan, Fengjuan; Yan, Han; Zhang, Yuyang; Huang, Zhenli; Sun, Chunyan; Hu, Yu (Frontiers in Oncology, 2020)
Background: The incidence of Waldenström macroglobulinemia (WM) has increased in certain groups over several decades in the United States. It is unclear whether the increasing incidence is associated with mortality trends. Methods: The incidence and incidence-based mortality (IBM) rates were obtained from the Surveillance, Epidemiology, and End Results (SEER) database (1980–2016) with SEER*Stat software. The secular trends stratified by demographic characteristics were analyzed by joinpoint regression. Results: The incidence of WM showed an initial rapid increase from 1980 to 1993 (annual percentage change (APC), 14.1% [95% confidence interval (CI), 10% to 18.4%]), whereas it began to stabilize from 1993 to 2016 (APC, 0.5% [95% CI, -0.3% to 1.3%]). The WM IBM trend followed a similar pattern, with a decrease occurring around 1994. The trends in incidence and mortality significantly differed according to geographic location, race, age, sex, primary site of involvement and subtype, which could help in further investigations into the specific etiology. Moreover, a dramatic increase in the five-year survival rate from the 1980s to 2010s was observed (47.84% vs 69.41%). Conclusions: Although both the incidence and IBM of WM continued to increase during the study period, a reduction in the rate of increase occurred around 1993. We believe that further advances in healthcare delivery and research can ensure a low mortality rate. Future studies can use the findings of this paper to monitor the results of WM therapy.